Students' English Language Development through the International VCL Module of the ValeuX project - Dorela Kaçauni (International School for Social and Business Studies, 2023)
Purpose: The purpose of this study is to investigate the development of students' English language in terms of speaking, pronunciation and vocabulary while their participation in the "International Virtual Collaborative Learning" (IVCL) Module under the framework of the Erasmus+ programme European Union funded Project: ValeuX: Virtual Albanian European Universities Exchange. Students from 8 Albanian and European universities participated in the ValeuX incubator for 6 weeks. They had to work on a business start-up concerning eco-tourism in Albania. During these weeks, students had to talk in English and schedule meetings to discuss the tasks they had to prepare. During this experience, they developed their English language skills. Study design/methodology/approach: The methodology of this paper is focused on a questionnaire distributed to 43 students via Google Forms to gather the data concerning the impact that students had after joining the "International VCL" Module and their development of different aspects of the English Language.  Findings: The findings showed that the student's English language development was noticeable. They perceived natural communication in English and expanded their vocabulary as well. Originality/value: This study is important because it brings into light an aspect of taking part in International Virtual Learning, which is the development of English Language skills. It was a Foreign Language for all the students, and they worked on designing a start-up business idea about eco-tourism in Albania.